2017
DOI: 10.1021/acs.jpcc.7b03910
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Observation of Reversible Surface Reconstruction of Copper Electrodes under CO2 Reduction

Abstract: The ability of copper to catalyze the electrochemical reduction of CO 2 has been shown to greatly depend on its nanoscale surface morphology. While previous studies found evidence of irreversible changes of copper nanoparticle and thin film electrodes following electrolysis, we present here the first observation of the reversible reconstruction of electrocatalytic copper surfaces induced by the adsorbed CO intermediate. Using attenuated total internal reflection infrared and surface-enhanced Raman spectroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
292
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(364 citation statements)
references
References 55 publications
39
292
3
5
Order By: Relevance
“…Figure S5). Interestingly, this surface morphology change at CO 2 ‐reduction potentials is qualitatively consistent with previous observations for Cu‐catalysts, and has recently been suggested to be triggered by surface‐adsorbed CO produced as a CO 2 ‐reduction intermediate . Moreover, the specific appearance of cracks in the TF is likely related to the reduction of the initial Cu 2 O to Cu 0 in the course of CO 2 ‐electroreduction (cf.…”
Section: Resultssupporting
confidence: 89%
“…Figure S5). Interestingly, this surface morphology change at CO 2 ‐reduction potentials is qualitatively consistent with previous observations for Cu‐catalysts, and has recently been suggested to be triggered by surface‐adsorbed CO produced as a CO 2 ‐reduction intermediate . Moreover, the specific appearance of cracks in the TF is likely related to the reduction of the initial Cu 2 O to Cu 0 in the course of CO 2 ‐electroreduction (cf.…”
Section: Resultssupporting
confidence: 89%
“…[24] Interestingly, the restructuring appears to occur at timescales comparable to the pulse duration. [24] Interestingly, the restructuring appears to occur at timescales comparable to the pulse duration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental and theoretical studies demonstrated that Cu(100) is the most favorable crystal orientation for the C−C coupling process . However, the surface of Cu electrodes under electrochemical environments often undergoes reconstructions induced by applied potentials, the intermediates formed during CO 2 RR, as well as specifically adsorbed anions . On the other hand, some anions either present in the electrolyte or adsorbed on the electrode surface, have been shown to play a vital role in the dynamic evolution of the catalyst structure under reaction conditions as well as the activity and selectivity of CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%